Center-Pivot-Irrigated Forage Sorghum Silage Cost-Return Budget in Western Kansas - Dumler, Troy J.; Thompson, Curtis R.; Stockton, Roger (My University, 2003)
This publication estimates the costs and returns associated with center-pivot-irrigated forage sorghum put up as silage in western Kansas.
MF998_2003_10
Keywords: MF998; Economics; Crops; MF